1988
DOI: 10.1111/j.1432-1033.1988.tb14004.x
|View full text |Cite
|
Sign up to set email alerts
|

The auto‐oxidation of tetrahydrobiopterin

Abstract: The product of the aerobic oxidation of tetrahydrobiopterin, quinonoid dihydrobiopterin, is unstable and rapidly rearranges to form a 7,s-dihydropteridine. Kaufman [Kaufman, S. (1967) J. Biol. Chem. 242,3934-39431 identified the stable product produced in 0.1 M phosphate pH 6.8, as 7,s-dihydrobiopterin. However, Armarego et al. [Armarego, W. L. F., Randles, D. and Taguchi, H. (1983) Eur. J. Biochem. 135 393-4031 questioned this assignment because they found that the dihydroxypropyl group on C-6 was eliminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
88
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 36 publications
(30 reference statements)
5
88
1
Order By: Relevance
“…As shown here, BH 2 is only degraded to a small extent in 30 min. Davis et al observed no degradation of BH 2 for up to 150 min at pH 6.8-8.2 (Davis et al, 1988), which is in line with our results showing little degradation during this short-time span. On the other hand, Dántola et al followed the degradation of BH 2 at neutral pH at 25°C for 2 days and observed very little degradation (Dántola et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As shown here, BH 2 is only degraded to a small extent in 30 min. Davis et al observed no degradation of BH 2 for up to 150 min at pH 6.8-8.2 (Davis et al, 1988), which is in line with our results showing little degradation during this short-time span. On the other hand, Dántola et al followed the degradation of BH 2 at neutral pH at 25°C for 2 days and observed very little degradation (Dántola et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…The half-life of BH 4 can be estimated to be around half an hour at pH 3 and at pH 4 and above almost complete oxidation takes place in 20 min (Lyudnikova et al, 2009). At pH 5.3-7.6 the half-life was estimated to around 9 min (Heales et al, 1988), and another study found half-lives of 6.5-60 min at pH 6.8-8.2 depending on the buffer used (Davis et al, 1988). Similarly, a half-life of 15-20 min was observed at pH 7.4 (Valent & Tóth, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…All the monoaminergic neurons and terminals in the CNS produce BH4 and DA cells are vulnerable to high level of BH4, most probably due to the higher rate of oxidation of DA compared with other catecholamine or serotonin [18,19]. Under, the normal conditions, the level of GTP-CH I expression in the nigrostriatal system is lower than in the other monoaminergic cells [23,24].…”
Section: Discussionmentioning
confidence: 96%
“…BH4 auto-oxidation could produce hydrogen peroxide and superoxide radical [18][19][20][21]. In addition, DA, with its synthesis facilitated by BH4, in turn undergoes auto-oxidation to form a reactive quinine species [18,22,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation